急速な増大による摂食・呼吸障害を生じた先天性ラヌーラの1例 - 前原, 香織; 小林, 武仁; 笹原, 庸由; 飯野, 光喜; 北畠, 健一朗; 熊本, 裕行 (日本口腔外科学会雑誌, 2023)
A ranula is a mucous cyst that forms on one side of the floor of the mouth as a result of damage to the excretory salivary duct. It is a common condition in young people, however congenital cases are rare. We report a case of congenital ranula that grew rapidly to a large size after a mass was noted on the left side of the floor of the mouth during the neonatal examination.　 A pea-sized mass was identified on the left side of the floor of the mouth during the neonatal examination. An MRI was performed at the age of 1 year and 2 months due to sleep apnea, snoring and a suckling disorder, and an egg-sized mass was found on the floor of the mouth. An experimental puncture aspiration was performed and the ranula was surgically removed under general anesthesia the next day. Histopathological findings showed a mucous extravasated lesion associated with extensive fibrosis with acute and chronic inflammatory cells, leading to a diagnosis of sublingual ranula.　The possibility of functional impairment such as breathing and suckling disorders should be fully considered in cases of congenital ranula, and follow-up and the timing of surgery should be carefully considered.